Novel Sepatu Dahlan Karya Krisna Pabichara Analisis Psikologi Sastra dan Nilai Pendidikan - Masnu'atul Hawa (IKIP PGRI Bojonegoro, 2014)
Sepatu Dahlan’ Novel by Khrisna Pabichara Analysis of Psychological Literature And Educational Values. This research is qualitative descriptive study using the approach of structuralism and psychological aspects of character with the methods and strategies for qualitative descriptive content analysis. Activities carried out reading, looking at, interpreting, and analyzing the novel Sepatu Dahlan. The results of the activity described in the form of sentences. This study aims to describe and explain (1) narrative structure, (2) the psychology of character, and (3) educational values embodied in the novel Sepatu Dahlan by Khrisna Pabichara. Thus research was descriptive qualitative research with content analisys method. The data or important informations were collected and studied in this research includes words from and the result is written in the document analysis. The technique which was used to collect the data was reading, writing, and analyzing on that novel. The validity data which was used was trianggulasi data, trianggulasi method, and trianggulasi theory: the technique analysis data wich was used in this research was analyzing interactive technique. The result of research on the pychology of the characters in the novel Sepatu Dahlan by Khrisna Pabichara includes: psychological needs, security needs, cherished and loved needs, esteem needs, and actualization. Further more, the educational values are religion, moral, social, economy, and culture.Key words: novel Sepatu Dahlan, psychology literature, educational values.